STUDI VEGETASI PADA HABITAT TARSIUS (Tarsius Sp.) DI DESA KAMARORA KAWASAN TAMAN NASIONAL LORE LINDU - Ekawati, Yuni; Labiro, Elhayat; Rukmi, Rukmi (Warta Rimba, 2013)
Tarsier (Tarsius sp.) are alboreal species which life on the trees. The vegetation is one of the important biotic factors for the wild animal as a place for food, nesting places and shelter from extrim weather and hide from predators. The study aims were to determine the spesies composition and association of vegetation of tarsius (Tarsius sp.) habitat in Kamarora village. Research methods using multiple plots placed by purposive sampling at tarsier habitat. The results showed that the species composition at all levels of the growth obtained thirty two plant species. Based on the analysis of Chi-square (X2) between species at each level of the growth (seedlings, saplings, pole and tree) obtained that twenty four plant significantly associated tangible and four plant species were associated very significant. Key words: Vegetation, Habitat, Tarsius sp., Lore Lindu National Park